Development of a method for regenerative braking of an electric scooter (Institute of Advanced Engineering and Science, 2023)
In this work, a method of regenerative braking of an electric scooter was developed. Regenerative braking of electric vehicles is the basis for energy saving cars and environmental protection. A stand was made for the study of a magnets and an ionistor. In the proposed method, an ionistor is additionally connected in parallel to the battery, which charges faster than the battery, so the process of accelerating the electric vehicle after stopping also occurs faster. It should also be noted that if emergency braking is necessary to stop an electric vehicle, the driver can press the brake pedal and stop the car using brake pads. The paper investigates the method of the element base for the vehicle, as well as control. To develop this study, an electric scooter was chosen as an electric vehicle model. The dependences of the electric current on the operating time of the ionistor in three positions are determined. During the actual speed of the electric scooter corresponds to the controlled speed.